Measuring submaximal endurance performance with hyperoxic gas - Sperlich, B.; Schiffer, T.; Hoffmann, U.; Mester, J.; Hollmann, W.; Strüder, H. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Numerous test procedures have been designed to quantify metabolic and respiratory function. Altering inspired oxygen concentration (FiO2) leads to several metabolic and cardio-respiratory reactions. HOLLMANN (1963) defined the so called "spirografic oxygen deficit" (SOD) as the excess oxygen uptake (V 02) above 100 ml/min after changing FiO2 from normoxia (NO) to hyperoxia (HE) during steady state load. The SOD was regarded as the sufficiency limit of submaximal endurance performance due to the limiting factors of peripheral oxygen consumption. The aim of the study was to determine whether the intensity at which SOD appears relates to an increase in lactate (La) accumulation.